Síntomasde Cancro Cítrico en Árbolesde Vivero - Timothy D. Riley; Megan M. Dewdney; Jamie D. Burrow (EDIS)
This is a two-page illustrated identification sheet for citrus canker symptoms that appear in citrus nurseries. Written by Timothy D. Riley, Megan M. Dewdney, and Jamie D. Burrow, and published by the UF Department of Plant Pathology, May 2013.